FORMULASI SEDIAAN GEL ANTISEPTIK EKSTRAK METANOL DAUN KESUM (Polygonum minus Huds) - ., Famella Yulistia Pramita (Jurnal Mahasiswa Farmasi Fakultas Kedokteran dan Ilmu Kesehatan UNTAN, 2013)
Chemical contents of Kesum (Polygonum minus Huds), such as phenolic, flavonoids, alkaloids, steroid-terpenoids and tannin, can act as antibacterial agent.The aims of this research was to determine whether methanol extract of kesumleaves have antibacterial effect and its effectivity when it was formulated in gelproduct. Extract activity test group being used are negative control, methanolextract 5%, 10% and 15%. Gel effectivity test group being used are negativecontrol, positive control, Gel A, (5% methanol extract), Gel B (10% methanolextract) and Gel C (15% methanol extract). Disc diffusion Kirby-Bauer methodwas used to determine the antibacterial effectivity against Escherichia coli. Gelstability test carried out for 31 days include organoleptic, viscosity, ability ofspreading and sticking and pH. The methanol extract 5%, 10% and 15% gaveantimicrobial effect. It was formulated in gel product with that concentrations.The result of the effectivity test and stability test were analyzed statistically bySPSS 17.0 using One-Way ANOVA and continued to Post Hoc Tukey Test.Diameter of the inhibition zone gel was Gel A (10.66 mm) Gel B (12.11 mm), GelC (12.33 mm). Gel C gave best antimicrobial effect between Gel A, Gel B andpositive control. So it has potensial to be antiseptic agent. In all variables of gelstability test, Gel C has a few changes, so Gel C stability is better than Gel A andGel B.Keywords: kesum leaves, gel, antiseptic, Escherichia coli